PESANTREN, ULAMA, DAN PEMBENTUKAN TRADISI ISLAM INDONESIA - Supani Supani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2011)
This article shows the Islamisation process in Indonesia using twotheories, Arab and India. In discussing this point there should be a differentiationbetween the first and the second theory. The first theory is representedby the real first relation between Indonesia Islam. Meanwhile thesecond theory shows the growing of some Islamic kingdoms. The style ofIslam spreading process is evolutionary as it could penetrate far beyondto Muslims consciousness.